2002
DOI: 10.1530/eje.0.1460089
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cholecystokinin 2-receptor in normal human thyroid gland and medullary thyroid carcinoma

Abstract: Objective: The cholecystokinin 2 -receptor (CCK 2 R) promotes secretion and cell growth induced by its ligands cholecystokinin (CCK) and gastrin. The receptor has recently been shown to be expressed in human medullary thyroid carcinomas (MTCs). The objective of this study was to analyze CCK 2 R expression in MTC samples of different tumor stages as well as in non-malignant thyroid tissues. Design and Methods: Using RT-PCR we investigated 19 MTC samples and TT-cells (a human MTC cell line), as well as samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…28), which may explain the brisk calcitonin response to pentagastrin seen in patients with MTC. There are indications that CCK 2 R is also expressed in normal parafollicular C cells (29). Glucagon-like peptide I also induces calcitonin mRNA in rat MTC cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…28), which may explain the brisk calcitonin response to pentagastrin seen in patients with MTC. There are indications that CCK 2 R is also expressed in normal parafollicular C cells (29). Glucagon-like peptide I also induces calcitonin mRNA in rat MTC cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, its receptor CCK2R, which is shared with gastrin, has been described to be expressed at different intensities in normal and malignant C cells by Blakër et al [218]. No additional data has been published with regard to the putative functional role of CCK signalling in thyroid, however, there are initial encouraging therapeutic results with the use of CCK/Gastrin R2-binding peptides in patients with MTC [219,220].…”
Section: Other C-cell Secreted Peptidesmentioning
confidence: 99%
“…Gastrin receptors have been detected in C-cells of the thyroid gland (Blaker et al 2002) and in the brain (Lee et al 1993), but have to our knowledge not been identified in bone. In the current study, PCR analyses of gastrin receptor expression in primary mouse osteoblasts and osteoclasts were also negative.…”
Section: Discussionmentioning
confidence: 95%